The effect of tourmaline on cell membrane of nitrosomonas europaea and biodegradation of micropollutant. (11th June 2014) - Qiu, Shan; Xu, Huang; Xu, Shanwen; Ma, Fang
<x xml:space="preserve">Abstract</x> As a kind of ammonia‐oxidizing bacteria, Nitrosomonas europaea (N. europaea) was chosen as a research model to study the alteration of cell membrane in the presence of tourmaline and biodegradation of acetochlor. atomic force microscopy images reveal that the presence of tourmaline substantially changes the structure of the outer membrane of the cell responsible for the cell permeability. SEM images show that the introduction of tourmaline makes the cell lose its ability to resist lysozyme owing to the damages. The fluorescence polarization has shown a significant decrease in membrane fluidity and the increase of permeability of cell membrane. Ca2+ and Mg2+ was measured using inductively coupled plasma mass spectrometry and was found in the supernatant from the cells treated by tourmaline. Tourmaline can improve the efficiency of biodegradation of acetochlor for N. europaea. It is proposed that the cell permeability is slightly increased, and the absorbability of nutrition from the medium becomes easier. As a result, N. europaea grows faster in the presence of tourmaline than the native cells. Copyright © 2014 John Wiley & Sons, Ltd.